The Sedimentology of the Late Campanian–Maastrichtian Sequence, Southwestern Iraq - Mazin Y. Tamar-Agha; Muzahim A. Basi (Iraqi Journal of Science, 2021)
Petrography, diagenesis, and facies analyses as well as the depositional environments of the late Campanian-Maastrichtian sequence in southwestern Iraq are studied in five keyholes. The sequence incorporates parts of the Hartha, Shiranish and Tayarat Formations. The Hartha Formation comprises creamy and organodetrital dolomite, grey dolomitic marl, and evaporites. The Shiranish Formation is composed of grey marl and claystone, whereas the Tayarat Formation is composed of grey ash, along with tough and fossiliferous dolomitic limestone inter-bedded with grey mudstone layers and/or wisps. Several diagenetic processes affected the sequence, such as neomorphic replacement, dissolution, dolomitization, and sulphate development. Some of these processes obliterated the primary textures.The late Campanian-Maastrichtian sequence consists of three microfacies (Dolomitic Intraclastic Limestone, Dolomitized Biomicrite, and Biomicrosparite Microfacies) and two lithofacies (Mudrock and Sulphates-Rock Lithofacies), in addition to Fine- to Medium-Crystalline Dolomite Lithotype.The Hartha Formation is evaporitic, possibly with supratidal sabkha deposits. The overlying Tayarat and Shiranish Formations reflect deposition in a warm tropical to subtropical reefal and open marine conditions, as deduced from faunal assemblages. Some effects of deep marine condition are evident by the presence of Shiranish facies. The sequence represents deposition in the central reef- fore reef area. The absence of isolated back-reef lagoon facies suggests that the reef was patchy without isolation of water in the middle shelf region. However, at the top of the sequence, i.e. at the end of the Cretaceous Period, restricted lagoons seem to have dominated the studied succession.